The use of violence ini llegal markets: evidence from mahogany trade in the Brazilian Amazon - Ariaster B. Chimeli; Rodrigo R. Soares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
Agents operating in illegal markets cannot resort to the justice system to guarantee property rights, to enforce contracts, or to seek protection from competitors' improper behaviors. In these contexts, violence is used to enforce previous agreements and to fight for market share. This relationship plays a major role in the debate on the pernicious effects of the illegality of drug trade. This paper explores a singular episode of transition of a market from legal to illegal to provide a first piece of evidence on the causal effect of illegality on systemic violence. Brazil has historically been the main world producer of big leaf mahogany (a tropical wood). Starting in the 1990s, policies restricting extraction and trade of mahogany, culminating with prohibition, were implemented. First, we present evidence that large scale mahogany trade persisted after prohibition, through misclassification of mahogany exports as “other tropical timber species.” Second, we document relative increases in violence after prohibition in areas with: (i) higher share of mahogany exports before prohibition; (ii) higher suspected illegal mahogany activity after prohibition; and (iii) natural occurrence of mahogany. We believe this is one of the first documented experiences of increase in violence following the transition of a market from legal to illegal.
Keywords: K42; O13; O17; Q58; 330; illegal markets; violence; homicide; mahogany; Brazil Jel Codes: K42; O13; O17; Q58; Cannabis; Drogenwirtschaft; Illegaler Handel; Gewalt; Normbefolgung; Brasilien